PENGARUH PEMBERIAN DIET TINGGI KARBOHIDRAT DIBANDINGKAN DIET TINGGI LEMAK TERHADAP KADAR TRIGLISERIDA DAN HDL DARAH PADA Rattus novergicus galur wistar - Tsalissavrina, Iva; Wahono, Djoko; Handayani, Dian (Jurnal Kedokteran Brawijaya, 2006)
ABSTRACT The improving social welfare and food availability has created a shift of consumption pattern that leads to high-fat foodsand low-complex carbohydrate, especially the fibrous foods.  As we know,carbohydrate has been considered as the safecomponent of foods, therefore, it is recommended to be consumed more. Recently, more experts have started to thinkabout the role of carbohydrate and the emergence of atherosclerosis. The Purpose of the research was to know the riskof high carbohydrate diet application compared to high fat blood triglyceride diet content and high Density Lipoprotein.Complete random design and Post Test Only Control Group was used in this research. Statistic test one way Anova wasused to know the difference resulted from diet aplication, and the situation of the difference continued  by Tukey   Test.The Value of Triglyceride is measured by using Calorimetric Enzymatic test – Glycerol 3 Phosphate –oxidase methodsand the value of HDL is measured by using Cholesterol Hydrolise – oxidase methods.  The result showed that the highestvalue of triglyceride were on the high fat diet group ( 169 mg/dl), followed by high carbohydrate diet ( 130,2 mg/dl) and thelowest was normal diet (81,2 mg/dl). The lowest value of HDL were on the normal diet group (32,7 mg/dl), followed byhigh fat diet (34,2 mg/dl) and the highest was high carbohydrate diet (38,4 mg/dl). The result of the statistical test over the